The Influence of Product Variety, Service Quality and Price on Purchasing Decisions (a Case Study on Customers of Miniso Central Park Mall Jakarta) - Hasriati, Hasriati; Istikomah, Kartini (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the effect of product variety, service quality, and price on purchasing decisions among customers of MINISO Central Park. The research employs a quantitative causal design with data collected through a structured questionnaire distributed to customers. The analysis was conducted using multiple regression to evaluate the validity, reliability, and statistical significance of the proposed relationships. The findings reveal that service quality and price significantly influence purchasing decisions, while product variety shows no substantial impact. The results suggest that customers place greater emphasis on the affordability of products and the quality of service they experience, rather than the diversity of product assortment. This highlights the importance of focusing on value creation and service excellence to strengthen consumer decision-making. The study contributes to marketing literature by providing evidence from a retail context and offers managerial implications for enhancing customer satisfaction and loyalty.